Green or lean? A supply chain approach to sustainable performance. (10th April 2019) - Huo, Baofeng; Gu, Minhao; Wang, Zhiqiang
Abstract: Based on a natural resource-based view, this study investigates how lean and green processes in manufacturer-customer (customer side) and manufacturer-supplier interfaces (supply side) in the supply chain influence sustainability in environmental, social, and economic performance. Data from 171 manufacturers are used to test the proposed relationships. The results show that green and lean processes play different roles in achieving sustainable performance. On the customer side, lean processes are the main driver of higher sustainable performance. The results show that lean processes directly improve social, environmental, and economic performance, while green processes improve only environmental performance. On the supplier side, green processes play a prominent role in reaching higher sustainable performance as they directly improve social and economic performance, while lean processes improve only economic performance. This study contributes to the supply chain management and sustainability literature and has managerial implications for firms to more effectively improve sustainable performance. Highlights: This study compared the roles of lean and green processes in supply chain. Lean process in customer interface improves all three sustainability performance. Lean process in supplier interface only improves economic performance. Green process in customer interface only improves environmental performance. Green process in supplier interface improves social and economic performance.